Chemical characterization and functional properties of selected leafy vegetables for innovative mixed salads - Mazzucotelli, Cintia Anabela (2018)
The content of bioactive compounds and antioxidant capacity of nine vegetables of conventional and unconventional utilization in salad mixtures were studied. The total phenolic and flavonoid contents ranged between 39.6–148.5 mg GAE/100g FW and 76.3–217.4 mg QE/100g FW, respectively. Ascorbic acid content ranged between 16.4 and 198.8 mg AAE/100g FW. Antioxidant capacity was assessed using DPPH, FRAP, and ORAC methods; values were in the range of 48.9–245.8 mg TE/100g FW, 67.7–335.8 mg TE/100g FW, and 104.86–833.9 mg TE/100g FW, respectively. Red cabbage, beet greens, parsley, and rocket exhibited the highest antioxidant capacities. Catechin was the most abundant phenolic compound identified in the free fraction, and p-coumaric acid, quercetin, and caffeic acid in the hydrolyzed fraction. Results suggested that the presence of these phenolics could be of great importance in preventing some chronic and degenerative diseases when regularly consumed. Nonconventional vegetables showed high antioxidant properties, therefore, it is important to promote their consumption. Practical applications: Not all vegetables have the same phenolic composition, and not all phenolics have the same antioxidant capacity. Knowledge of the bioactive content and antioxidant capacity profile in each vegetable could be of interest to consumers and the food industry for selecting the more suitable leaves to make salad mixtures with high nutritional and functional values. These compounds can prevent some chronic-degenerative diseases related to oxidative stress, so it is important introduce them regularly into the diet. Moreover, the evaluation of nontraditional vegetables is intended to bring consumers toward a new source of bioactive compounds, prompting their consumption, and providing added value to certain plant parts that are sometimes considered as waste products.